PENGGUNAAN TEPUNG KOMPOSIT DARI TERIGU, PATI SAGU DAN TEPUNG JAGUNG DALAM PEMBUATAN ROTI TAWAR - Rahmah, Anania; Hamzah, Faizah; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to obtain best combination composite flour (wheat flour, sago starch, corn flour) on the quality of white bread produced. This research was carried out experimentally using completely randomized design (CRD) with five treatments and four replications in order obtain twenty experiment units. The treatments in this study were TSJ0 (100% wheat flour), TSJ1 (70%wheat flour :30% sago starch), TSJ2 (70% flour : 20% sago starch : 10% corn flour), TSJ3 (70% wheat flour : 10% sago starch : 20% corn flour) and TSJ4 (70% wheat flour : 30% corn flour). Data obtained were treated by the analysis of variance folowed by Duncan New Multiple Range Test (DMRT) the level of 5%. The results showed that the addition of sago starch and corn flour at different concentration levels significantlyaffectedon the moisture, ash, protein, fat and carbohydrate contents as well as, hedonic test, descriptive test the colour, aroma, flavor and texture of white bread. The best treatment was TSJ3, with a moisture content of 24.33%, ash content of 1.03%, fat content5.67%, protein content of 8.05%,carbohydrate levels60.92%, as well as sensory acceptable by panelist.Keywords: white bread, sago starch, corn flour.